India's fragmented social protection system: Three rights are in place; Two are still missing - Santosh Mehrotra; Neha Kumra; Ankita Gandhi (United Nations Research Institute for Social Development (UNRISD), 2014)
In India, 22 per cent of the population lives below the poverty line and 93 per cent is employed informally, despite the fact that India is the second fastest-growing economy after China. Nevertheless, in a positive trend, Indias welfare system has increasingly moved towards a rights-based approach, as opposed to treating Indias citizens as mere recipients of state-provided benefits. This paper discusses the key role of civil society mobilization and political support that has led to the implementation of the principles of the Right to Work (albeit mostly in rural areas), the Right to Education and the Right to Food in India. On the other hand, both Indias social insurance system and its public health system remain limited in coverage and fragmented in character. As large numbers of Indians remain vulnerable to poverty on account of health expenditures, it is imperative that all have access to universal preventive and public health services, and that, among those who work in the unorganized sector, at least the poor have full social insurance coverage (old age pensions, death and disability insurance, maternity benefits). Furthermore, in the absence of publicly provided health care, such insurance should give this segment of the population access to a preventive and basic curative health care package. Our paper touches only briefly upon the issue of social insurance because achieving this is a medium-term goal which the Indian welfare state must work towards within current fiscal constraints. We focus primarily on the performance and the weaknesses of the health system. We find that the governments flagship health insurance scheme for the poor, the Rashtriya Swasthya Bima Yojana, is ineffective in providing financial risk protection with respect to health care, has inadequate coverage, and does not cover out-of-hospital consultations. We argue on behalf of universal health coverage in India and suggest the following areas for immediate policy intervention in the health sector: First: All doctors should be required to serve in rural areas regardless of whether this is required for a post graduate degree. Second: There is a strong case for introducing a three-year course for rural practice in all states. Third: More regular staff and paramedics are needed to manage services and as front-end providers of services. Fourth: the essential drug procurement system needs to be revamped. Fifth: the safe sanitation programme must become more effective if the nutrition and health status of citizens is to improve.
Keywords: 330